Authorial Stance in Government News on Social Media Age Restrictions: A Comparative Analysis of Indonesian and English Discourse - Afriliani Afriliani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study examines how epistemic stance is linguistically realized across two institutional genres addressing children's digital protection: an Indonesian government policy corpus (Data A, 908 words) and an Australian research report (Data B, 1,490 words). Employing a quantitative corpus-based discourse analysis, the study identifies and compares the distribution of epistemic stance markers across three analytical categories, namely cognitive attitude, epistemic modality, and epistemic justification, developed inductively from the data. The findings reveal a striking asymmetry in both density and distribution: the policy corpus deploys markers at nearly three times the rate of the research corpus (89.21 vs. 32.89 per 1,000 words), with cognitive attitude dominating at 58% of policy markers, while epistemic justification accounts for 84% of research markers. These results indicate that the two corpora construct institutional authority through fundamentally different epistemic logics, with the policy text commanding through normative evaluation and deontic assertion, and the research report persuading through evidential accountability and methodological transparency. The study contributes to cross-genre discourse analysis by demonstrating that comparative examination of institutional texts addressing the same social issue can reveal epistemic patterns invisible in single-genre studies, and affirms that stance is always shaped by communicative purpose, audience design, and institutional ideology.